Technological Integration in Management Curriculum - Omiegbe, Odirin; Osagiede, Mercy Afe (NIU Journal of Educational Research, 2024)
Curriculum is the programme of instruction students are exposed to in the teaching and learning process. It is all the teaching and learning activities teachers and students are engaged in a formal school system from the beginning of the course of study or training to the end. For effective utilization of the curriculum there is the need for proper classroom management which involves students, subject matter, learning materials and learning environment in an orderly manner. However, the educational system is witnessing digital transformation driven by technological advancement which seems promising. To keep pace with this novel phenomenon and benefit from the usage, management education needs to equip teachers with the knowledge and skills necessary to leverage this technological advancement through its integration in curriculum. This paper therefore examines the technology to be deployed to the classroom for effective management of students, its benefits, potential approaches and considerations for successful implementation. Keywords: Technology, Educational Technology, Integration, Classroom Management, Curriculum.